Analysis of the COVID-19 pandemic’s impacts on manufacturing: a systematic literature review and future research agenda - Ardolino, Marco; Bacchetti, Andrea; Ivanov, Dmitry (Operations management research, 2022)
The COVID-19 pandemic has affected manufacturing companies and necessitated adaptations of firms’ operations. Despite the increasing interest in this subject, a scarcity of systematic analysis can be observed. The present study systematically reviews the existing research on the COVID-19 pandemic concerning the manufacturing industry. This paper aims to highlight the main impacts of the COVID-19 pandemic on the manufacturing sector from the operations management perspective, the practical adaptation actions, and future research opportunities. Open research questions and directions for further investigation are articulated and triangulated across organisational, process and technology perspectives.